2020
DOI: 10.1016/j.celrep.2020.107755
|View full text |Cite
|
Sign up to set email alerts
|

TRPM5 Negatively Regulates Calcium-Dependent Responses in Lipopolysaccharide-Stimulated B Lymphocytes

Abstract: B cells produce high amounts of cytokines and immunoglobulins in response to lipopolysaccharide (LPS) stimulation. Calcium signaling cascades are critically involved in cytokine production of T cells, and the cytosolic calcium concentration is regulated by calcium-activated monovalent cation channels (CAMs). Calcium signaling is also implicated in B cell activation; however, its involvement in the cytokine production of LPSstimulated B cells remains less well characterized. Here, we show that the transient rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 47 publications
2
10
0
Order By: Relevance
“…We then used the expanded EBCs to assess the impact of major signaling pathways which have been implicated in the determination of cell fate during lung development. The tested pathways include Tgfß/Bmp, Yap, Shh, Wnt, Notch, IL-6 and IL-4/IL-13 (Ahdieh et al, 2001;Barkauskas et al, 2013a;Ikonomou et al, 2020;Lee et al, 2014b;Li et al, 2017;Nabhan et al, 2018;Pardo-Saganta et al, 2015;Tadokoro et al, 2014;Vaughan et al, 2015;Yuan et al, 2019;Zacharias et al, 2018). We observed that treatment with IL-4 or IL-13 apparently promoted tuft cell derivation from EBCs in air-liquid interface (ALI) culture (data not shown), in agreement with the previous reports of IL-4Rα-dependent tuft cell expansion from the intestinal crypts (Gerbe et al, 2016;von Moltke et al, 2016).…”
Section: Inhibition Of Wnt and Notch Signaling Has Opposite Effects O...supporting
confidence: 92%
See 1 more Smart Citation
“…We then used the expanded EBCs to assess the impact of major signaling pathways which have been implicated in the determination of cell fate during lung development. The tested pathways include Tgfß/Bmp, Yap, Shh, Wnt, Notch, IL-6 and IL-4/IL-13 (Ahdieh et al, 2001;Barkauskas et al, 2013a;Ikonomou et al, 2020;Lee et al, 2014b;Li et al, 2017;Nabhan et al, 2018;Pardo-Saganta et al, 2015;Tadokoro et al, 2014;Vaughan et al, 2015;Yuan et al, 2019;Zacharias et al, 2018). We observed that treatment with IL-4 or IL-13 apparently promoted tuft cell derivation from EBCs in air-liquid interface (ALI) culture (data not shown), in agreement with the previous reports of IL-4Rα-dependent tuft cell expansion from the intestinal crypts (Gerbe et al, 2016;von Moltke et al, 2016).…”
Section: Inhibition Of Wnt and Notch Signaling Has Opposite Effects O...supporting
confidence: 92%
“…Trpm5 is a calcium-activated channel protein that induces depolarization in response to increased intracellular calcium (Prawitt et al, 2003). It is also expressed in B lymphocytes in addition to tuft cells (Sakaguchi et al, 2020). We observed decreased accumulation of B lymphocytes in the lungs of Trpm5 -/- mutants following viral infection (unpublished data, H.H.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the strong correlation between circulating bacterial DNA and leukocyte populations may be explained by a cross-talk between the intestinal microbiota and bone marrow during bacterial infection, which induces increased myelopoiesis ( Balmer et al, 2014 ). Moreover, circulating lipopolysaccharide is associated with activation and proliferation of lymphocyte subsets as observed for NK cells and B-cells ( Ramendra et al, 2019 ; Sakaguchi et al, 2020 ). Interestingly, high levels of blood bacterial DNA were found associated with increased insulin and glucose levels.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, an analysis of TRPM5 rs886277 polymorphism in the Genotype-Tissue Expression (GTEx) Portal [53], a public resource that provides data of tissue-specific gene expression and regulation according to variant data, showed this polymorphism had been described as an expression quantitative trait loci (eQTL), the C allele and CC genotype being linked to lower TRPM5 expression in pancreas. Moreover, since a sustained inflammatory response is involved in liver injury, it is interesting to note that TRPM5 deficiency in mice increases inflammatory cytokine production in B lymphocytes following lipopolysaccharide stimulation and exacerbates endotoxic shock severity [42]. These studies suggest that defects in the expression or functionality of TPRM5 may promote a sustained inflammatory response contributing to fibrosis progression and cirrhosis development.…”
Section: Discussionmentioning
confidence: 99%
“…TRPM5 is a Ca 2+ -impermeable channel that modulates cellular Ca 2+ entry, determines the membrane potential, and regulates nerve signals and insulin secretion [14,15]. In a negative feedback loop, Ca 2+ activates TRPM5 to promote Na + influx, which induces membrane depolarization and a subsequent decrease in the driving force for Ca 2+ entry [14,42,43]. TRPM5 is present in pancreatic β-cells, where it modulates glucose metabolism.…”
Section: Discussionmentioning
confidence: 99%